Initial Assessment of Heavy Metals in Urban Farming Produce - Valenzuela, Vergel G.; Kwan, Charita S.; Responde, Abegail R.; Ilagan, Adriel John R.; Bondoc, Jonah L.; Dom-ogen, Elizabeth T. (Science Diliman: A Journal of Pure and Applied Sciences, 2024)
The study investigated the levels of heavy metals (Hg, As, Cd, Cr, Pb) in frequently consumed vegetables in urban and rural farms in the Philippines and assessed their associated health risks. Results revealed that the Hg concentration was at method detection limit (MDL), while for other heavy metals, the values ranged from Cr>As>Cd>Hg. Single factor ANOVA demonstrated a significant difference (α = 0.05) between urban and rural sites. Assessment of noncarcinogenic risk by combined impact of all metals (Hazard Index, HI) indicated no concern (<1) for both adults and children for Hg, Cd, Cr and Pb except for As in taro and red chili (HI: 1.2 – 1.9) from specific urban sites. The carcinogenic risk by Target Cancer Risk (TCR) assessment was >10E–5 (USEPA limit) for As (1.8E-4 to 7.9E-4) and Cr (1.2E–4 to 1.2E-3) exposing future risk from long-term consumption of contaminated vegetables. While urban farming produce can serve as food source for the community, review of regulatory measures is recommended to avert potential health risks.